2022
DOI: 10.3389/fpsyg.2022.922402
|View full text |Cite
|
Sign up to set email alerts
|

Role of Resistance to Innovation, Lack of Intercultural Communication, and Student Interest on the Student Demotivation Results Towards the English Education System

Abstract: Recently, second-language learning success depends upon the students' interest and motivation by adopting innovations that require regulators' and new researchers' emphasis. Hence, this article explores the role of resistance to innovation, lack of intercultural communication, and students' interest on the students' demotivation. The article also examines the mediating role of students' demotivation among resistance to innovation, lack of intercultural communication, lack of students' interest, and failure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…The present findings in terms of self-construal support the related notion that researchers ensured positive linkages with the learning process from various dimensions and perspectives across the world (Cross et al, 2000, 2011; Fry et al, 2008; Gorham & Christophel, 1992; Hattie, 1999; Lund Dean & Jolly, 2012; Ma & Li, 2023; Mahu, 2012). Similarly, several studies support and validate our findings showing consistency with our results in terms of demotivation, disengagement, and learning process of the students from various dimensions and perspectives across the world (Çankaya, 2018; Cocea & Weibelzahl, 2010; Kızıltepe, 2008; Lund Dean & Jolly, 2012; Unal & Yanpar Yelken, 2016; Vidak & Sindik, 2018; J. Wang & Pan, 2022; S.…”
Section: Discussionsupporting
confidence: 90%
“…The present findings in terms of self-construal support the related notion that researchers ensured positive linkages with the learning process from various dimensions and perspectives across the world (Cross et al, 2000, 2011; Fry et al, 2008; Gorham & Christophel, 1992; Hattie, 1999; Lund Dean & Jolly, 2012; Ma & Li, 2023; Mahu, 2012). Similarly, several studies support and validate our findings showing consistency with our results in terms of demotivation, disengagement, and learning process of the students from various dimensions and perspectives across the world (Çankaya, 2018; Cocea & Weibelzahl, 2010; Kızıltepe, 2008; Lund Dean & Jolly, 2012; Unal & Yanpar Yelken, 2016; Vidak & Sindik, 2018; J. Wang & Pan, 2022; S.…”
Section: Discussionsupporting
confidence: 90%
“…According to earlier research, ERI is a kind of demotivation that has been found to have a detrimental impact on people's willingness to use information technology (Wang and Pan, 2022).…”
Section: The Mediating Role Of Capabilities Of Employeesmentioning
confidence: 99%
“…According to earlier research, ERI is a kind of demotivation that has been found to have a detrimental impact on people’s willingness to use information technology ( Wang and Pan, 2022 ). According to Alomari et al (2014) , ERI was one of the factors that led to the non-adoption and failure of new information systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the aspects of a person that can influence learning outcomes is interest in learning (Gray et al, 2020;Lería et al, 2022;Rudianto et al, 2022). The teaching and learning process of some students can be classified as having high learning interest, moderate and not a few students whose learning interest is relatively low, especially in mathematics (Pelaccia & Viau, 2017;Rajprasit et al, 2022;Wang & Pan, 2022). Student learning outcomes will be maximised when students are highly interested in mathematics.…”
Section: Introductionmentioning
confidence: 99%